PERFORMANCE LABORATORY OF ASPHALT CONCRETE WEARING COURSE ( AC-WC) WITH SUBTITUSI BUTON GRANULAR ASPHALT ( BGA) 15/20 FROM LAWELE AS SMOOTH AGGREGATE - MARWAZY ANAS (NIM : 26906005), MHD.
Asphaltic concrete pavement tends to suffer from premature failure caused by traffic loadings. To improve the performance of the asphalt mixes and to utilize local material, it is suggested that Buton Granular Asphalt (BGA), as a partial substitution of bituminous material, can be used. The objective of this research is to evaluate in the laboratory characteristic of resilient modulus and permanent deformation of asphalt concrete wearing course ( AC-WC) with substitution of BGA Lawele 15/20. The mixes was prepared based on the 2007 specification for hot mix asphalt. The Optimum Bitumen Content (OBC) was determined using the Marshall and the PRD is method. Three types of mix were studied i.e. AC-WC without BGA (BGA-0), AC-WC with 5% BGA (BGA-5) and AC-WC with 10% (BGA-10). The OBC of BGA-0, BGA-5, and BGA-10 was 6,24%, 6.16%, and 6.71% respectively, while the Index of Retained Strength (IKS) was 89,04%, 90,93%, and 95,57%. The values of Marshall Stability was 1200,80 Kg, 1244,30 Kg, and 1346,13 Kg respectively. while the value of Resilient Modulus was 955,7 Mpa, 1023 Mpa and 1068 Mpa at 35 oC and 471,2 Mpa, 451,7 Mpa and 532,8 Mpa at 45 oC. The value of Total Deformation (d0) was 2,76 mm, 2,06 mm, 1,82 mm, while tha value of Dynamic Stability was 4846,2 cycles/mm, 7875 cycles/mm, 5250 cycles/mm, for BGA-0, BGA-5 and BGA-10, respectively. In general, the BGA-10 mix appears to have better mix performance, regarding all values of Marshall Stability,Index of Retained Strenght, Resilient Modulus at 35 oC and 45 oC, and total Deformation at 45 oC, compared to the other mixes.